2009
DOI: 10.1001/archinternmed.2009.175
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme Inhibitors and Cognitive Decline in Older Adults With Hypertension

Abstract: Background Hypertension (HTN) is a risk factor for dementia and animal studies suggest that centrally active (cross the blood brain barrier) angiotensin converting enzyme (ACE) inhibitors may protect against dementia beyond HTN control. Methods Participants in the Cardiovascular Health Study cognition substudy (mean age 75 yrs) with treated HTN and no diagnosis of heart failure (n= 1054) were followed for a median of 6 years to determine whether cumulative exposure to ACE inhibitors (as a class and by centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
200
4
10

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(219 citation statements)
references
References 43 publications
4
200
4
10
Order By: Relevance
“…The similar pharmacologic effects of the ACE inhibitors on cognitive function were also found in recent clinical trials [9][10][11] and in animal models [12,13]. It is noteworthy that some studies denoted that the direct effects of the ACE inhibitors to lower the risk of developing dementia could be independent from the controlling of cardiovascular disease and blood pressure control [2,4,14]. Nevertheless, these inconsistent results have also been reported in other studies [4,[15][16][17][18].…”
supporting
confidence: 66%
See 2 more Smart Citations
“…The similar pharmacologic effects of the ACE inhibitors on cognitive function were also found in recent clinical trials [9][10][11] and in animal models [12,13]. It is noteworthy that some studies denoted that the direct effects of the ACE inhibitors to lower the risk of developing dementia could be independent from the controlling of cardiovascular disease and blood pressure control [2,4,14]. Nevertheless, these inconsistent results have also been reported in other studies [4,[15][16][17][18].…”
supporting
confidence: 66%
“…They indicated that the introduction of an ACE inhibitor in order to block the ACE activity might not only reduce the benefits to Aβ degradation [42,43], but also decrease the potential harm of Angiotensin II action on either acetylcholine release or hypertension. In addition, the inhibition of an ACE activity in the brain has also been reported to associate with cognitive improvement via increasing substance P, diminishing inflammatory cytokines, suppressing reactive oxygen species generation, or improving cerebral blood flow [2,4,6,12]. In addition to the well-known functions of an ACE enzyme as mentioned above, the physiological implications of ACE continue to expand, in which ACE has been found to exert many other functions than is usual and is localized in different brain tissues.…”
Section: Pharmarcogenetic Mechanism Of Ace I/d Polymorphism Adverselymentioning
confidence: 99%
See 1 more Smart Citation
“…46,47) In previous studies regarding HT and dementia, ARBs and ACE inhibitors with a higher degree of BBB penetration could prevent the development of dementia; however, this preventative effect was not confirmed in randomized controlled trails. 48,49) Thus, the precise mechanisms by which ARBs and ACE inhibitors affect psychiatric and cognitive functions are yet unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Advancing age, comorbid conditions, and cumulative drug exposures contribute to long-term health outcomes among persons with chronic diseases [1][2][3]. Historically, observational studies using administrative pharmacy claims characterize drug exposure as either dichotomized variables or as cumulative CrossMark ← Click for updates doi: 10.7243/2054-9911-3-2 exposure for drug class, combination regimens, or specific drugs [4].…”
Section: Introductionmentioning
confidence: 99%